Validitas Petunjuk Praktikum Bioteknologi Berbasis Guided Inquiry untuk Peserta Didik SMA di Kabupaten Sumbawa Barat - Fitri Rahmawati; Sahratullah Sahratullah (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to determine the validity of guided inquiry-based biotechnology practicum guidelines for high school students in West Sumbawa Regency. The development model used in this research is the 4D development model, with details of the stages, namely: 1) define; 2) design / design; 3) develop / development; and 4) disseminate / spread. This research uses a quantitative descriptive approach. The research data were collected using instruments, namely validation sheets (construct and content) for two expert validators, as well as legibility test sheets for high school students. The research sample consisted of 28 students of class XII IPA at SMAN 2 Taliwang. The data from the validation results were analyzed using the mean score analysis and validation criteria. The results showed that, the results of the validation by constructors were very valid with a mean score of 3.75 and a percentage of 93.75% with very good criteria. The results of the validation by content experts were valid with a mean score of 3.17 and a percentage of 87.51% with very good criteria. While the legibility test results showed the mean score of all aspects assessed was 68.61 and the percentage value was 71.47% with easy criteria. The conclusion of this study is that guided inquiry-based biotechnology practicum instructions for students can be applied in practicum activities on Biotechnology material for class XII IPA SMA in West Sumbawa Regency.